Muscle strength, aerobic capacity, and exercise tolerance are impaired in left ventricular assist devices recipients: A pilot study - Gobbo, Stefano; Favro, Francesco; Bullo, Valentina; Cugusi, Lucia; Blasio, Andrea Di; Bortoletto, Alessandro; Bocalini, Danilo Sales; Gasperetti, Andrea; Ermolao, Andrea; Bergamin, Marco (Frontiers in Physiology, 2022)
Background: Left ventricular assist devices (LVAD) are increasingly being used as a therapy for advanced heart failure, both as a bridge to heart transplant and, given the rapid advances in the LVAD’s functionality and safety, and constant lack in availability of donor organs, as long-term destination therapy. With the diffusion of such therapy, it is crucial to assess patients’ muscle strength, aerobic capacity and exercise tolerance, to improve their functional capacity. Methods: 38 LVAD recipients (33 men and 5 women) were included. Exercise testing including a maximal cardiopulmonary exercise test (CPET), handgrip, isometric and isokinetic strength testing of knee and ankle flexion/extension, and Romberg balance test in three conditions (eyes open, eyes closed, double task). Given the small and heterogeneous final sample size, a mostly descriptive statistical approach was chosen. Results: 12 participants were classified as “Obese” (BMI>29.9). The most common comorbidities were type II diabetes and chronic kidney disease. Only 12 participants were able to successfully complete all the assessments. CPET and isokinetic strength trials were the least tolerated tests, and the handgrip test the best tolerated. Mean VO2 peak was 12.38±3.43 ml/kg/min, with 15 participants below 50% of predicted VO2 max, of which 6 below 30% VO2max. Mean handgrip strength was 30.05±10.61 Kg; 25 participants were below the 25° percentile of their population’s normative reference values for handgrip strength, 10 of which were below the 5° percentile. Issues with the management of the external pack of the LVAD and its influence on the test limited the validity of the balance tests data, therefore, no solid conclusions could be drawn from them. VO2 peak did not correlate with handgrip strength or with any of the lower limb strength measures. Conclusion: LVAD recipients show greatly reduced functional capacity and tolerance to exercise and exercise testing, with low overall strength levels. As strength variables appear to be independent from VO2 peak, different lower limbs strength tests should be explored to find a tolerable alternative in this population, which is subjected to muscle wasting due to old age, reduced tissue perfusion, side effects from the pharmacological therapies, and prolonged periods of bedrest.